Diversity of Trees Species in The Natural Ecosystems of Development Area for Eco-Forest Green Open Space at Pangkalan Kerinci City, Indonesia - Nawari Nawari; Aras Mulyadi; Rasoel Hamidy; Tengku Nurhidayah (Riau University, 2021)
Eco-Forest green open space (GOS) development is one of the ways to achieve sustainable urban development in Pangkalan Kerinci City. The information of structure and composition of the natural tree species growing in the green open space was required as a basis to formulating future rehabilitation strategy. This study aims to analysed the diversity and composition of tree species at the development area of Eco-Forest GOS. The data used in this study was primary data of tree species, dbh, frequency and density. Data collected by field observation using a systematic sampling method. Data analysis was carried out by estimate the diversity parameters including diversity index, richness, and evenness. Species composition assessed by important value index. Spatial interpolation of the diversity index and tree density was carried out by spline interpolation method using ArcGIS 10.7 software. The analysis result shows that the diversity of natural tree species was decreases by increasing the live cycle of tree. There are three dominant species in this location, which Ilexcymosa, Litsea firma, and Stemonurus secundiflorus. Spatial analysis shows that 51.5% of the green space area classified into low diversity and density category, while 13.2% was classified as high diversity and density class. Efforts to achieved the successful of GOS management by use the information of vegetation’s structure and composition as one of the inputs to develop the regeneration and rehabilitation system. At the same time, it is necessary to increases the dimensions of human, institutional and financial management that supports biodiversity conservation in the green open space